Association of NRAMP1 Polymorphisms with Immune Traits in Indonesian Native Chickens - Muhsinin, M.; Ulupi, N.; Gunawan, A.; Wibawan, IWT.; Sumantri , C. (International Journal of Poultry Science, 2016)
Background: Natural resistance-associated macrophage protein-1 gene (NRAMP1) plays an important role in immune response against intracellular pathogens. Objective: This study was aimed at identifying NRAMP1 polymorphisms and their association with immune traits in Indonesian native chickens. Methodology: Genetic polymorphism of chickens was investigated using polymerase chain reaction-restriction fragment polymorphism. The concentrations of leukocytes and differentiation (heterophile, lymphocyte and monocyte) were assessed by the Giemsa method and immune traits were detected by followed clearance test. Results: The results showed that NRAMP1 was polymorphic in all native chickens. The CC genotype was significantly higher than CT and TT genotypes (p